Qallunology- A Pedagogy for the Oppressor. - Derek Rasmussen (2001)
Canada's Euro-descended ruling elite says to Inuit: 'The land that used to root you we have taken; the human arrangements that used to connect you we have broken; the pattern-languaged face-to-face myths and stories that once flowed between you and your place we have frozen onto paper. Now we will 'educate' you to master alphanumeric symbols in order to make money from us in order to get access to the land (we took from you) and in order to buy the essentials of life. This is the Euro-American way.'